2016
DOI: 10.1016/j.ijfatigue.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser shock processing on high cycle fatigue crack growth rate and fracture toughness of aluminium alloy 6082-T651

Abstract: The effects of laser shock processing without protective coating on high-cycle fatigue crack growth and fracture toughness were investigated. Laser shock peening treatment was performed on compact tension specimens from both sides perpendicular to the crack growth direction, followed by subsequent grinding. Fatigue crack growth tests were performed at frequencies between 116 and 146 Hz, at R=0.1 and a constant stress intensity range during the fatigue crack initiation phase and K-decreasing test. A lower numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 20 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…The retardation effect of LSP on the FCP rate was attributed to high compressive residual stresses, which were generated in 2 mm-thick AA2024 sheets. Bergant et al (2016) [1] observed an inferior FCP behaviour of 10 mm-thick 6082-T651 C(T) specimens with LSP compared to that of BM specimens. The reason was probable in the unoptimised LSP process, which resulted in higher surface roughness without introducing noticeable compressive residual stresses in the investigated material.…”
mentioning
confidence: 93%
“…The retardation effect of LSP on the FCP rate was attributed to high compressive residual stresses, which were generated in 2 mm-thick AA2024 sheets. Bergant et al (2016) [1] observed an inferior FCP behaviour of 10 mm-thick 6082-T651 C(T) specimens with LSP compared to that of BM specimens. The reason was probable in the unoptimised LSP process, which resulted in higher surface roughness without introducing noticeable compressive residual stresses in the investigated material.…”
mentioning
confidence: 93%
“…Further, the effects on chemical composition after LSP and geometric [17] analyzed the effect of pulse density on low cycle fatigue in super-ferritic stainless steel and it is observed that the LSP causes thermal effects on the surface microstructure, generating intergranular corrosion, which decreases the fatigue life of this alloy. Bergant et al [18] founded that the LSP increases fatigue crack growth rate in 6082-T651 Al alloy due the equilibrium tensile stresses in the center of specimen and notches edge as explained by Correa et al [5,7] through MEF simulation. Granados-Alejo et al [19] analyzed the effect of samples thickness in 2205 DSS, in which it is observed that in thinner samples, higher fatigue life is obtained by LSP.…”
Section: Introductionmentioning
confidence: 98%
“…The results clearly demonstrated that LSP can be used as an effective surface treatment technique for reducing or suppressing fatigue crack growth in aluminium alloys. However, application of a not optimised LSP process can produce high surface roughness without introducing noticeable compressive residual stresses [10]. In this case, LSP can reduce the fatigue life of critical components and structures.…”
Section: Introductionmentioning
confidence: 99%